2009
DOI: 10.3928/00220124-20090923-02
|View full text |Cite
|
Sign up to set email alerts
|

Using a Mentorship Model to Prepare Newly Graduated Nurses for Competency

Abstract: This research was conducted to study the level of nursing competency of newly graduated nurses after using a mentor-ship model. Nineteen newly graduated nurses worked with a trained mentor. Before the experiment, newly graduated nurses were evaluated regarding their nursing competency by head nurses two times, with a 1-month interval between evaluations. Select experienced nurses were prepared in mentoring roles. The mentors and the newly graduated nurses worked together for 1 month. After that, newly graduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 7 publications
2
51
0
3
Order By: Relevance
“…Komaratat and Oumtanee, 62 reported that levels of competency had significantly increased by the end of the mentorship period.…”
Section: Competencymentioning
confidence: 99%
See 2 more Smart Citations
“…Komaratat and Oumtanee, 62 reported that levels of competency had significantly increased by the end of the mentorship period.…”
Section: Competencymentioning
confidence: 99%
“…Using a mentorship model to prepare newly graduated nurses for competency. 2009 Komaratat and Oumtanee, 62 investigated the level of nursing competency of newly graduated nurses (n=19) after using a mentorship model. The research was conducted within one hospital in Thailand using a quasi experimental one group time series approach.…”
Section: Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The competency of new graduates increases after the implementation of such a mentorship program [21]. From the moment new graduates begin their residency at Vidant Medical Center, they are paired with a mentor who best matches their personality and has at least 2 years of clinical experience.…”
Section: Solutionsmentioning
confidence: 99%
“…Nurse mentoring programs increase new nurses' intent to stay and retention rates [20]. For new graduates to achieve competency, confidence, and autonomy, organizations need a structured approach to developing mentors [21]. In 2000, Morton-Cooper and Palmer [22] introduced a mentorship model that includes 3 phases.…”
Section: Solutionsmentioning
confidence: 99%